Revisiting Death: Implicit Bias and the Case of Jahi McMath - Goodwin, Michele (The Hastings Center report, 2018)
For nearly five years, bioethicists and neurologists debated whether Jahi McMath, an African American teenager, was alive or dead. While Jahi's condition provides a compelling study for analyzing brain death, circumscribing her life status to a question of brain death fails to acknowledge and respond to a chronic, if uncomfortable, bioethics problem in American health care—namely, racial bias and unequal treatment, both real and perceived. Bioethicists should examine the underlying, arguably broader social implications of what Jahi's medical treatment and experience represented. On any given day, disparities in the quality of health care and health outcomes for people of color in comparison to whites are evidenced in American hospitals and clinics. These disparities are not entirely explained by differences in patient education, insurance status, employment, income, expressed preference for treatments, and severity of disease. Instead, research indicates that, even for African Americans able to gain access to health care services and navigate institutional nuances, disparities persist across a broad range of services, including diagnostic screening and general medical care, mental health diagnosis and treatment, pain management, HIV-related care, and treatments for cancer, heart disease, diabetes, and kidney disease.